THE EFFECT OF TAX AMNESTY, TAX KNOWLEDGE AND ONLINE TAX SERVICES ON PERSONAL TAXPAYER COMPLIENCE IN ACEH BESAR DISTRICT - Susanti, Eva; icut, Cut Fitrika Syawalina; budi, Budi Safatul anam (J-ISCAN: Journal of Islamic Accounting Research, 2023)
In the last 10 years the realization of tax revenue has always been below the target, with the achievement of a tax ratio of 11% -13%. The poor situation in taxation is inseparable from low tax compliance, illegal flight of capital abroad, engineering financial transactions that result in a loss of potential tax revenues. Entering 2015 the tax office has implemented an online tax service system and it peaked in 2019 when the Covid pandemic occurred. Public services carried out in government agencies have experienced changes that have an impact on the accessibility of public services. be reduced. Good tax knowledge is expected to increase taxpayer awareness of the implementation of tax obligations. This study aims to determine the effect of tax amnesty, tax knowledge and tax services on compliance with tax payments by private taxpayers in Aceh Besar District. The data analysis technique in this study is multiple linear regression analysis by distributing questionnaires. The results of the study stated that tax amnesty, knowledge of taxation and tax services had an effect on compliance with personal taxpayer payments in Aceh Besar District.